Pengaruh Penerapan Good Corperate Governance Terhadap Kinerja Lembaga Perkreditan Desa (LPD) Se-Kecamatan Tabanan - Swari, Ni Made Ari Artika; Satriya, I Wayan Budi (Hita Akuntansi dan Keuangan, 2024)
Good Corporate Governance is a concept used to create a system that regulates and controls the company's management properly by taking into account the interests stakeholder such as government, administrators, community, and village manners within the LPD environment. The GCG principles are Transparency, Accountability, Responsibility, Independence and Fairness. The purpose of this study was to determine the effect of GCG on the performance of village credit institutions.The theory in this study uses agency theory.This research was conducted in Tabanan District, Tabanan Regency with a total population of 80 people consisting of 12 LPDs. The sampling technique used is saturated sampling technique, where all members of the population are used as samples. The analysis technique used is multiple linear regression analysis with data collection methods using a questionnaire.Based on the results of the research, it shows that transparency, accountability, responsibility, independence and fairness have a positive and significant effect on the performance of village credit institutions. The results of this study can be used as a reference to provide additional important information and input Good Corporate Governanve. By taking the components on GCG principles which include: Transparency, Accountability, Responsibility, Indepedency dan Fairness. By implementing good corporate governance, companies are expected to be able to reduce agency conflicts and be able to improve and maintain a company's performance.